Digital geocomputational technologies for the metaproject of urban green infrastructures - Valeria D’Ambrosio; Ferdinando Di Martino; Marina Rigillo (Agathón)
The paper presents a model to evaluate the ecological efficiency of urban green areas to support the meta-design of ‘green infrastructures’. The model was implemented with a GIS-based framework to extract ecological efficiency maps. The model was experimented in the case study area of Naples, Italy and aims to relate the different ecological capacities with the medium- and long-term heat wave impact scenarios on the population subject to energy poverty. The results of the experiment validate the model in terms of usability and replicability highlighting its added value as a support tool for decision-makers, in particular for the meta-design of green infrastructures in urban areas.